Lung carcinoma after radiotherapy and chemotherapy for Hodgkin's disease. Issue 5 (October 1977) - Matthay, R A; Zorn, S K; Mitchell, M S; Papac, R J
Abstract : Two patients, aged 29 and 40, with nodular sclerosing Hodgkin's disease, in complete remission for four and six years respectively after intensive radiotherapy and combination chemotherapy, developed carcinoma of the lung in the previous radiation port. Although radiotherapy and chemotherapy can eradicate Hodgkin's disease involving the thorax, this treatment may be associated with the development of a secondary pulmonary malignancy, particularly in a previous radiation port, and several years may elapse before the new tumour becomes evident.